Latin America's eclusive democracies - Sorj, Bernardo (Centro Edelstein, 2021)
This is a refreshing book: it contains nothing trite, rejects conventionality and academic fads, and unswervingly asserts a clear position on thorny issues. With this book, Bernardo Sorj has demonstrated once again what those of us who have followed his career already knew: not only is he an excellent sociologist, but above all, he is a true intellectual, a critical thinker who tackles the main issues of today’s world, and Latin America in particular.